2012
DOI: 10.3758/s13414-012-0369-x
|View full text |Cite
|
Sign up to set email alerts
|

Speed has an effect on multiple-object tracking independently of the number of close encounters between targets and distractors

Abstract: Multiple-object tracking (MOT) studies have shown that tracking ability declines as object speed increases. However, this might be attributed solely to the increased number of times that target and distractor objects usually pass close to each other ("close encounters") when speed is increased, resulting in more target-distractor confusions. The present study investigates whether speed itself affects MOT ability by using displays in which the number of close encounters is held constant across speeds. Observers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 54 publications
(171 reference statements)
2
25
0
1
Order By: Relevance
“…This result is not 426 surprising knowing that the ability to maintain attention on multiple stimuli or 427 locations for quite a prolonged period of time is important for sport (Memmert, 428 2009). Importantly the 3D-MOT technique includes speed thresholds as a 429 dependent variable which is considered as a crucial part of MOT performance by 430requiring more attentional resources to track at higher speeds(Feria, 2012).431 Recently, neurological evidence has demonstrated the role of 3D-MOT in 432 improving attention, visual information processing speed and working memory 433(Parsons, et al, 2014). From other imagery studies, the MOT technique has 434 reported activation of higher-level brain areas involved in attentional processes…”
mentioning
confidence: 99%
“…This result is not 426 surprising knowing that the ability to maintain attention on multiple stimuli or 427 locations for quite a prolonged period of time is important for sport (Memmert, 428 2009). Importantly the 3D-MOT technique includes speed thresholds as a 429 dependent variable which is considered as a crucial part of MOT performance by 430requiring more attentional resources to track at higher speeds(Feria, 2012).431 Recently, neurological evidence has demonstrated the role of 3D-MOT in 432 improving attention, visual information processing speed and working memory 433(Parsons, et al, 2014). From other imagery studies, the MOT technique has 434 reported activation of higher-level brain areas involved in attentional processes…”
mentioning
confidence: 99%
“…Results from these studies reveal key factors for people's performance in MOT tasks: speed, trajectory, and spacing. Increasing objects' moving speeds impairs tracking accuracy and decreases the maximum number of targets people can track [1,9,26], except for one case when the speed is changed by scaling the display as a whole [10]. Suganuma and Yokosawa found that the tracking accuracy is also impaired when targets share similar trajectories with distractors [27].…”
Section: Introductionmentioning
confidence: 94%
“…Objects' moving speed is one key factor for people's tracking performance in MOT tasks [1,9,26]. To ensure a fair comparison, we chose to control objects' average moving speed in this study, i.e., 0.5 units per second for both types of trajectories.…”
Section: Experimental Design and Task Generationmentioning
confidence: 99%
See 2 more Smart Citations